Mental health, bullying and school connectedness: A comparative analysis of school transition at age 11 from within the Welsh education system - Donaldson, Caitlyn; Morgan, Kelly; Page, Nicholas; Angel, Lianna; Moore, Graham (British Educational Research Journal)
While transition from primary to secondary school is a positive experience for many young people, for others, it may be a difficult period of adjustment. Socioeconomic status (SES) may influence the likelihood of a positive or negative transition experience owing to differences in psychosocial (self-esteem, self-efficacy, social support) and flexible (cultural capital, financial support, power) resources to respond to the challenges presented by a new school environment. Welsh all-age schools do not have a typical primary to secondary school transition and offer an opportunity for comparative analysis to explore the impact of transition on young people. This analysis used multilevel and structural equation modelling to assess differences in mental health and bullying outcomes in year 7 (first year of secondary education) in young people in all-age schools compared with those in secondary schools. It also considered whether school connectedness might explain these differences. It found that school type did not significantly predict outcomes at a population level; however, there was evidence of an interaction between SES and school attended for some outcomes. Peer problems, conduct problems and bullying victimisation were lower for children with low SES when attending all-age schools. For children with high SES, the same outcomes tended to be more positive if the children attended secondary schools. There was no evidence that school connectedness mediated the relationship between school type and mental health or bullying outcomes. Findings provide tentative evidence that all-age schools may act to reduce health inequalities caused by SES.
Keywords: all-age schools; mental health; school transition; socioeconomic status